The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12264-009-1215-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of edaravone against cobalt chloride-induced apoptosis in PC12 cells

Abstract: Objective To investigate the neuroprotective effects of edaravone (Eda) on cobalt chloride (CoCl 2 )-induced oxidative stress and apoptosis in cultured PC12 cells as well as the underlying mechanisms. Methods PC12 cells impaired by CoCl 2 were used as the cell model of hypoxia. MTT (methyl thiazolyl tetrazolium) was used to assay the viability of the PC12 cells exposed to Eda with gradient concentrations; Hochest 33258 stain assay was used to analyze the apoptosis ratio of the PC12 cells; Bcl-2 and Bax protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…27,28 Our preliminary results showed that CoCl 2 was able to induce HIF-1a at 100 and 500 mM concentrations (Supplementary Figure 2). However, higher concentrations (>500 mM) resulted in apoptosis of ACL fibroblasts (Supplementary Figure 3) therefore, 100 and 500 mM concentration of CoCl 2 were used in the experiments.…”
Section: Cocl 2 -Induced Hif-1a Increases Mmp-2 Activitymentioning
confidence: 87%
“…27,28 Our preliminary results showed that CoCl 2 was able to induce HIF-1a at 100 and 500 mM concentrations (Supplementary Figure 2). However, higher concentrations (>500 mM) resulted in apoptosis of ACL fibroblasts (Supplementary Figure 3) therefore, 100 and 500 mM concentration of CoCl 2 were used in the experiments.…”
Section: Cocl 2 -Induced Hif-1a Increases Mmp-2 Activitymentioning
confidence: 87%
“…Cobalt chloride (CoCl 2 ) is a well-known hypoxia mimetic agent. These CoCl 2 -elicited biochemical changes include the production of ROS, a loss of mitochondrial membrane potential, activation of hypoxia inducible factor 1a (HIF-1a) and the expression of a number of genes, such as erythropoietin, vascular endothelial growth factor and endothelin-2/vasoactive intestinal contractor (one of the hypoxia-related factors) (Chandel et al 1998;Guillemin and Krasnow 1997;Yang et al 2004;Zou et al 2002;Kotake-Nara and Saida 2007;Chen et al 2009Chen et al , 2010bYang et al 2011b).…”
Section: Cobaltmentioning
confidence: 99%
“…It is reported that one of the mechanisms underlying CoCl 2 -induced neuronal damage is associated with the production of ROS (Zou et al 2002;Chen et al 2009;Jung et al 2008). CoCl 2 could function as an oxidative stress-inducing factor since Co(II) can react with H 2 O 2 via Fenton-like reaction to produce ROS (Wang et al 1993).…”
Section: Cobaltmentioning
confidence: 99%
“…Cobalt chloride (CoCl 2 ) is a well-known hypoxia mimetic agent. There are numerous reports that CoCl 2 mimics the hypoxia response in a number of aspects in various cultured cells, including production of reactive oxygen species (ROS), a loss of mitochondrial membrane potential (MMP), activation of hypoxia inducible factor 1α (HIF-1α) and the expression of a number of genes, such as erythropoietin (EPO), vascular endothelial growth factor (VEGF) and endothelin-2 (ET-2)/vasoactive intestinal contractor (one of the hypoxia-related factors) (1)(2)(3)(4)(5)(6)(7)(8). Therefore, PC12 cells (a cell line derived from rat pheochromocytoma) exposed to CoCl 2 have been used to investigate events and mechanisms underlying neuronal cell death under conditions of hypoxia/ischemia (4,6,9).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that one of the mechanisms of CoCl 2 -induced neuronal damage is associated with its production of ROS (4,6,9). Elevated ROS is capable of attacking nucleic acids, proteins and membrane phospholipids, leading to neuronal apoptosis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%